Hot Cities A Transdisciplinary Agenda - Steele, Wendy (Edward Elgar Publishing, 2023)
Shedding light on the future of urban spaces, this path-breaking book is a significant contribution to contemporary climate change scholarship. It synthesizes interdisciplinary research with practical policy, putting an emphasis on positive environmental and socially just outcomes and urban regeneration.